Fibromyalgia Symptom Severity and Psychosocial Outcomes in Fibromyalgia Patients with Hypovitaminosis D: A Prospective Questionnaire Study. Issue 12 (5th February 2020) - D'Souza, Ryan S; Lin, Ge; Oh, Terry; Vincent, Ann; Orhurhu, Vwaire; Jiang, Li; Mauck, William D; Qu, Wenchun
Abstract: Objective: To evaluate the association between hypovitaminosis D and outcomes of symptom severity, mood disorders, fatigue, and quality of life in fibromyalgia (FM) patients. Methods: Five hundred ninety-three FM patients were surveyed from May 2012 to November 2013. Patients with serum vitamin D <25 ng/mL were considered to have hypovitaminosis D. The primary outcome was FM symptom severity (FIQ-R questionnaire). Secondary outcomes included quality of life (SF-36), fatigue (MFI-20), anxiety (GAD-7), and depression (PHQ-9). Independent t tests and chi-square tests were performed for continuous and categorical variables, respectively. Regression analysis was performed adjusting for age, gender, body mass index, ethnicity, and season. A post hoc analysis examined for correlation between outcomes and serum vitamin D (ng/mL) as a continuous variable. Results: One hundred twenty-two patients (20.6%) had hypovitaminosis D. In our adjusted regression analysis, the total FIQ-R score in patients with hypovitaminosis D was higher compared with control patients with adequate serum vitamin D (57.85 ± 18.09 vs 62.79 ± 18.10, P = 0.04). Adjusted regression analysis revealed higher total GAD-7 ( P = 0.01) and higher total PHQ-9 scores ( P = 0.04) in patients with hypovitaminosis D compared with control patients. There were no differences based on severity of depression or anxiety. No differences in fatigue or quality of life were identified. Unadjusted post hoc analysis revealed that as serum vitamin D increased, there was an association with lower total FIQ-R (β coefficient = –0.11, P = 0.02) and lower SF-36 subscale scores of role-physical (β coefficient = –0.10, P = 0.03). Adjusted post hoc analysis revealed no significant associations. Conclusions: Hypovitaminosis D may be a risk factor for worse symptom severity, anxiety, and depression in FM patients.